Sistem Informasi Pelacakan Tracer Study Berbasis Web Program Studi D3 Manajemen Informatika - Peniarsih, Peniarsih (Universitas Dirgantara Marsekal Suryadarma, 2016)
information Management Diploma Program Suryadarma University has alumni spread across various regions in Indonesia. Among them is by distributing questionnaires by post, email, mailing, graduation ceremony, the alumni meetings, and so forth. In addition, interviews were conducted with the alumni in person or by telephone. By looking at activity Tracer Study authors assume innovation still needs to be done to improve the activity tracer study. Given the development of web-based technology and internet media are increasingly mushrooming among the people of Indonesia, one of the innovations that can be done to activity tracer study is to develop a means in the form of a website that can be accessed by alumni, with the assumption that the internet has been reached by the majority of alumni. Information System Web-based to assist the tracer Study aims to increase the means activity tracer in terms of data collection and provide information in the form of reports on the results of data collection tracer study in accordance with the format specified by the Program Management Diploma Informatics University Suryadarma, information systems that will be made is expected to helps user satisfaction data collection activities of the Information Management Diploma Program graduates Suryadarma University.